FRI0112 Ethnic minority rheumatoid arthritis consortium (EMRAC): A prospective clinical database. (23rd January 2014) - Kerr, G.; Yazici, Y.; Sherrer, Y.; Nair, R.; Treadwell, E.; Mosley-Williams, A.; Espinoza, L.; Garcia-Valladares, I.; Ince, A.; Huang, J.; Nunziato, C.; McCracken, W.A.; et al.
Abstract : Background: Sparse data exist regarding minority ethnic groups with RA. EMRAC was developed to accrue prospective RA related clinical data in "real-world" settings serving ethnic minority patients in the United States. Methods: RA of self-reported ethnicity, and seen at 9 US sites are enrolled. Patient demographics, comorbidities, disease-related characteristics are collected. Analyses of overall differences in clinical variables between racial groups was performed using Kruskal-Wallis for continuous variables and exact tests for qualitative variables; post-hoc pairwise comparisons between racial groups were made with the Wilcoxon rank sum test and were adjusted using the Bonferonni correction (p<0.008 for significance). Results: To date, 502 RA patients have been enrolled (Table 1 ). Significant differences amongst ethnic groups were observed in age, education, RAPID3, DMARD use, biologics use, and the comorbidities of hypertension, diabetes, and cigarette use ever. African Americans were on the least amount of biologics, whereas Caucasians had least amount of disease activity compared to African Americans and Hispanics. All comorbid conditions were more common among minorities compared to Caucasians. Conclusions: EMRAC provides important clinical data in an underrepresented population, the results of which may help address differences in medication use and potential challenges in access and guide interventions that improve outcomes. Disclosure of Interest: G. Kerr Grant/Research support from: Genentech and Biogen IDEC, Inc, Y. Yazici Grant/Research support from: Abbott, BMS, Centocor, Genentech, Consultant for: Abbott, BMS, Genentech, Celgene, UCB, Y. Sherrer Grant/Research support from: AstraZeneca, Mercke, UCB, Sanofi Adventis, Celgene, Lily, Roche, Amgen, Wyeth, Pfizer, Novartis, Speakers Bureau: AstraZeneca, Human Genome Science, Amgen, Pfizer, Wyeth, R. Nair: None Declared, E. Treadwell: None Declared, A. Mosley-Williams: None Declared, L. Espinoza: None Declared, I. Garcia-Valladares: None Declared, A. Ince: None Declared, J. Huang: None Declared, C. Nunziato: None Declared, W. McCracken: None Declared, C. Swearingen: None Declared